Clinical assessment of chloramine-T and freshwater as treatments for the control of gill amoebae in Atlantic salmon, Salmo salar L - Harris, JO; Powell, MD; Attard, M; DeHayr, L (2005)
Infections of gill amoebae that manifest as amoebic gill disease (AGD) occur in Atlantic salmon in Tasmania. The treatment of choice is freshwater bathing; however, the effectiveness of this treatment has declined over time. In this experiment, cage trials of chloramine-T (Cl-T) to treat AGD in Atlantic salmon were conducted over 3 months, and involved an initial bath in either freshwater or seawater with Cl-T, followed by a second bath 6 weeks later. Amoeba densities were reduced to 50-80% of original values for both treatments. Neoparamoeba sp. density was not affected by bathing, and was not significantly different over the course of the experiment. Lesion prevalence was higher for Cl-T-treated fish than for freshwater-treated fish, with overall prevalence levels of 14.30 ± 1.00% and 8.03 ± 0.57% respectively. This was also seen for gross gill scores. In the fortnight after each of the two baths, Cl-T-treated fish had significantly higher lesion levels, although this difference was then resolved by 4 weeks post bathing. The use of Cl-T in seawater is at least as effective as freshwater at reducing amoebae density, and may be a more practical alternative when freshwater is in short supply. © 2005 Blackwell Publishing Ltd.